2014
DOI: 10.18637/jss.v056.i12
|View full text |Cite
|
Sign up to set email alerts
|

Introducinglocalgauss, anRPackage for Estimating and Visualizing Local Gaussian Correlation

Abstract: Quantifying non-linear dependence structures between two random variables is a challenging task. There exist several bona-fide dependence measures able to capture the strength of the non-linear association, but they typically give little information about how the variables are associated. This problem has been recognized by several authors and has given rise to the concept of local measures of dependence. A local measure of dependence is able to capture the "local" dependence structure in a particular region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…An introduction to the R package “localgauss ” for estimation and visualization of local dependence is available in Berentsen, Kleppe, and Tjøstheim ().…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An introduction to the R package “localgauss ” for estimation and visualization of local dependence is available in Berentsen, Kleppe, and Tjøstheim ().…”
mentioning
confidence: 99%
“…More details concerning the local Gaussian theory can be found in andTjøstheim and Hufthammer (2013).11 An introduction to the R package "localgauss" for estimation and visualization of local dependence is available inBerentsen, Kleppe, and Tjøstheim (2014). BAMPINAS AND PANAGIOTIDIS | 1183…”
mentioning
confidence: 99%
“…Since, from Section 5, we indicated that the best power is the one after standardization and normalization of the data set, we decided to study these examples after that transformation. To each data set, we apply the function localgauss.indtest() of the R‐package localgauss to obtain the graphics of Figures (for more details, see Berentsen et al , ). To perform the test, we use the test functional T1=[]()ρn(x1,x2)2dFn(k)(x,y)12.…”
Section: Examples With Real Datamentioning
confidence: 99%
“…In Figures b and b, the point x is magenta if the local correlation ρ n ( x ) is significantly positive, cyan if ρ n ( x ) is significantly negative and white when the null hypothesis is not rejected (see Berentsen et al , , for more details).…”
Section: Examples With Real Datamentioning
confidence: 99%
See 1 more Smart Citation